2011
DOI: 10.1029/2010jg001525
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical controls on methane, nitrous oxide, and carbon dioxide fluxes from deciduous forest soils in eastern Canada

Abstract: [1] The exchange of the important trace gases, methane (CH 4 ), nitrous oxide (N 2 O), and carbon dioxide (CO 2 ), between forested soils and the atmosphere can show great temporal and spatial variability. We measured the flux of these three gases over 2 years along catenas at two forested sites, to determine the important controls. Well-drained soils consumed atmospheric CH 4 , while poorly drained swamp soils embedded in depressions were a source. CH 4 fluxes could be predicted primarily by temperature and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
82
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 55 publications
13
82
4
2
Order By: Relevance
“…In our study, we did not find any agerelated differences for organic matter turnover when comparing litterfall and decomposition rates among the three older sites. Decomposition rates were within the range of those previously reported for other Canadian coniferous forests (Moore et al, 1999;Trofymow et al, 2002) and appeared to be unaffected by either stand age or site quality. In contrast, age-related differences in the litterfall rates were apparent when comparing the 35-and 70-year-old stands, with the latter one having higher rates (but similar SI values).…”
Section: Site Quality Effect On the Cumulative Nepsupporting
confidence: 66%
See 2 more Smart Citations
“…In our study, we did not find any agerelated differences for organic matter turnover when comparing litterfall and decomposition rates among the three older sites. Decomposition rates were within the range of those previously reported for other Canadian coniferous forests (Moore et al, 1999;Trofymow et al, 2002) and appeared to be unaffected by either stand age or site quality. In contrast, age-related differences in the litterfall rates were apparent when comparing the 35-and 70-year-old stands, with the latter one having higher rates (but similar SI values).…”
Section: Site Quality Effect On the Cumulative Nepsupporting
confidence: 66%
“…Using a process-based model, Inatomi et al (2010) similarly found that the GHG balance was mainly driven by the CO 2 exchange in a 50-year-old cool-temperate deciduous forest. However, the contribution of non-CO 2 GHG could be substantial in poorly drained locations within temperate forests (Ullah and Moore, 2011). The relative contribution of CH 4 and N 2 O to the forest GHG balance might further be considerably affected by more frequent freeze-thaw events (Luo et al, 2012;Teepe et al, 2001), altered N input (Liu and Greaver, 2009) as well as by contrasting forest management and tree growth responses to climatic changes in the future (Metsaranta et al, 2011;Ximenes et al, 2012).…”
Section: Forest Ghg Balance Across Stand Age and Site Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although many studies have quantified the magnitude and variability of CH 4 fluxes, they often covered large spatial extents (from transects that are tens of meters to hundreds of kilometers long) which captured significant environmental gradients at those scales, but sampling locations were generally sparse (Del Grosso et al, 2000;Yu et al, 2008;Teh et al, 2014;Tian et al, 2014). The smaller-scale patterns of CH 4 fluxes within these landscapes has not been investigated as thoroughly as ecosystem scale gradients, which could be problematic if those patterns are important for estimating CH 4 fluxes Ullah and Moore, 2011;Nicolini et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A spatially explicit understanding of heterogeneity in CH 4 fluxes is necessary for appropriate watershed scale budgets (Ullah and Moore, 2011;Bernhardt et al, 2017), particularly in mountainous regions, where the spatial distribution of resources could have a significant influence on the direction and magnitude of CH 4 fluxes due to the lateral redistribution of water and substrates caused by convergent and divergent areas of the landscape (Davidson and Swank, 1986;Meixner and Eugster, 1999;Wachinger et al, 2000;von Fischer and Hedin, 2002). Although many studies have quantified the magnitude and variability of CH 4 fluxes, they often covered large spatial extents (from transects that are tens of meters to hundreds of kilometers long) which captured significant environmental gradients at those scales, but sampling locations were generally sparse (Del Grosso et al, 2000;Yu et al, 2008;Teh et al, 2014;Tian et al, 2014).…”
Section: Introductionmentioning
confidence: 99%